FABRIKASI DAN KARAKTERISASI ANTENA MIKROSTRIP PATCH RECTANGULAR DENGAN SLOT PERSEGI PANJANG & SLOT T PADA GROUNDPLANE UNTUK FREKUENSI WiFi (2,4 GHZ) - Nailatus Saidah; Vira Rahayu (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
WIFI is a device that can facilitate to access information. Currently, electromagnetic waves are used in the transmission of internet network data, for example WIFI. The use of a WIFI network requires a device capable of transmitting or receiving electromagnetic waves, antenna. One of the antenna models that can be implemented is the microstrip antenna. Microstrip antenna has a lightweight design and low cost in its fabrication process. This study aims to design a microsrip antenna that is able to work at WIFI frequency (2.4 GHz). The shape of the patch used is rectangular, with rectangular slots, and has a groundplane that has a T slot. The antenna is designed on a circuit board (PCB) with a permittivity of 4.6 and a thickness of 1.6 mm. Furthermore, the antenna is simulated using the CST Suite 2017 software. The results obtained antenna criteria, such as: Retun Loss -40.66dB, VSWR 1.012, Gain 5.31 dBi, Bandwidth 4.09% and transmission pattern is directional.